1998
DOI: 10.1016/s0022-5223(98)70210-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of mitral valve repair for myxomatous disease with and without chordal replacement with expanded polytetrafluoroethylene sutures

Abstract: Mitral valve repair was feasible in most patients with mitral regurgitation caused by myxomatous disease and it was associated with low rates of valve-related complications. Chordal replacement with expanded polytetrafluoroethylene had no adverse effect on the late outcome and was believed to have increased the probability of mitral valve repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
131
1
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(145 citation statements)
references
References 19 publications
9
131
1
4
Order By: Relevance
“…Previous reports have described the incidence of repair failure and recurrence of severe MR being equally low with chordal replacement and quadrangular resection. 3,13,17) Results of this series were similar, whereby at 6 years, freedom from severe MR and freedom from reoperation were not significantly different between patients undergoing leaflet resection compared to those undergoing chordal reconstruction. More recent studies have reported freedom from reoperation rates favouring the non-resectional approach.…”
Section: Discussionmentioning
confidence: 64%
“…Previous reports have described the incidence of repair failure and recurrence of severe MR being equally low with chordal replacement and quadrangular resection. 3,13,17) Results of this series were similar, whereby at 6 years, freedom from severe MR and freedom from reoperation were not significantly different between patients undergoing leaflet resection compared to those undergoing chordal reconstruction. More recent studies have reported freedom from reoperation rates favouring the non-resectional approach.…”
Section: Discussionmentioning
confidence: 64%
“…The non-use of an annuloplasty ring, non-use of a sliding plasty, and the use of chordal shortening instead of transposition or artificial chordae were factors of recurrence of mitral valve incompetence, as already shown by others. 7 In a larger study, Gillinov et al 6 demonstrated that the instantaneous risk of reoperation (hazard function) consists of 2 hazard phases: a peaking early hazard phase in the first year after the operation, followed by a slow rising late hazard phase of reoperation. He showed that patients with an isolated anterior leaflet prolapse had an increased early risk of reoperation.…”
Section: Factors Influencing Post-repair Durabilitymentioning
confidence: 99%
“…Although these reports present up to 10-year follow-up results of survival, improved postoperative status, or freedom from reoperation, they do not describe echocardiographic follow-up of recurrence of mitral valve regurgitation. [3][4][5][6][7][8][9][10] The goal of the present study is to analyze the recurrence of mitral regurgitation in terms of incidence and degree in a series of patients undergoing mitral valve repair for degenerative disease. All patients were operated on in the same institution, by the same surgeon, and with the use of standard repair techniques.…”
mentioning
confidence: 99%
“…All these outcomes of our preliminary series may point that MV repair is an extremely safe in MR. The reported advantages of MV repair over MV replacement include preservation of LV function, greater freedoms from endocarditis, thromboembolic events, and anticoagulant-related hemorrhage (1)(2)(3)(4). In patients with MR, valve repair is preferred to valve replacement and allows an improved survival as well as higher quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures are feasible in almost 95% of patients with degenerative MR despite the presence of complex lesions (3). The operative mortality and morbidity for isolated mitral valve repair is low, and early failures are uncommon in experienced hands (4)(5)(6)(7). While the repair for the prolapse of the posterior leaflet with valvular resection is usually possible, correction of anterior or bileaflet prolapse may also be feasible with more complex repair procedures.…”
Section: Introductionmentioning
confidence: 99%